A high dielectric constant non-fullerene acceptor for efficient bulk-heterojunction organic solar cells. Issue 2 (12th December 2017) - Liu, Xi; Xie, Boming; Duan, Chunhui; Wang, Zhaojing; Fan, Baobing; Zhang, Kai; Lin, Baojun; Colberts, Fallon J. M.; Ma, Wei; Janssen, René A. J.; Huang, Fei; Cao, Yong
Abstract : A non-fullerene acceptor with a high relative dielectric constant ( ε r ) over 9 is developed. It offers an efficiency of 8.5%, which is the best result for organic solar cells employing high ε r materials. Further research should focus on morphology optimization to make high ε r practically useful in devices. Abstract : The majority of organic semiconductors have a low relative dielectric constant ( ε r < 6), which is an important limitation for organic solar cells (OSCs). A high dielectric constant would reduce the exciton binding energy, reduce charge carrier recombination losses, and thereby enhance the overall device performance of OSCs. However, the development of organic/polymeric semiconductors with higher relative dielectric constants ( ε r > 6) has attracted a very limited attention. Moreover, high performance OSCs based on high dielectric constant photovoltaic materials are still in their infancy. Herein, we report an oligoethylene oxide side chain-containing non-fullerene acceptor (ITIC-OE) with a high relative dielectric constant of ε r ≈ 9.4, which is two times larger than that of its alkyl chain-containing counterpart ITIC. Encouragingly, the OSCs based on ITIC-OE show a high power conversion efficiency of 8.5%, which is the highest value for OSCs that employ high dielectric constant materials. Nevertheless, this value is lower than those of ITIC-based control devices. The less phase-separated morphology in blend films due to the reduced crystallinity of ITIC-OE and the too good miscibility between PBDB-T and ITIC-OE are responsible for the lower device performance. This work suggests additional prerequisites to make high dielectric constants play a significant role in OSCs.